2021
DOI: 10.1371/journal.pone.0245131
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with multimorbidity among primary care patients with decreased renal function

Abstract: Objectives To establish the prevalence of multimorbidity in people with chronic kidney disease (CKD) stages 1–5 and transiently impaired renal function and identify factors associated with multimorbidity. Design and setting Prospective cohort study in UK primary care. Participants 861 participants aged 60 and older with decreased renal function of whom, 584 (65.8%) had CKD and 277 (32.2%) did not have CKD. Interventions Participants underwent medical history and clinical assessment, and blood and urine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Chronic kidney disease (CKD) is one of the most common diseases in adult age, and it is typical of older adults [1][2][3][4][5][6][7]. Recent data suggest that almost half of the elders have CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is one of the most common diseases in adult age, and it is typical of older adults [1][2][3][4][5][6][7]. Recent data suggest that almost half of the elders have CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney failure rarely occurs without the presence of other chronic diseases. Diabetes, hypertension and cardiovascular disease are associated with developing CKD [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…We identified five studies that examined the association between kidney function and multimorbidity cross-sectionally [27][28][29][30][31] . Four studies were conducted among CKD patient cohorts in Europe (k = 2) and Asia (k = 2), while one was based on ambulatory data from a statutory health insurance company in Germany.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…Three studies looked at the association between eGFR (continuous) and multimorbidity. A study from the UK found that in a cohort of patients with impaired renal function (CKD stages 1-5), there was an inverse association between eGFR at study entry and the odds of multimorbidity, defined as the co-occurrence of two or more diseases 28 indicates that this condition did not cluster with CKD; Empty cell indicates that the disease was not considered in this study. SPPB: short physical performance battery (higher score indicates better physical performance); COPD: chronic obstructive pulmonary disease.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%